2020
DOI: 10.3390/su12156198
|View full text |Cite
|
Sign up to set email alerts
|

How to Characterize Business Excellence and Determine the Relation between Business Excellence and Sustainability

Abstract: A descriptive attribute or characteristic of an object is called dimension. In the area of Business Excellence, this concept is associated with national quality awards and Business Excellence models. The aim of the paper is to identify the Business Excellence dimensions, on the grounds of comparative analysis of selected national quality award models, including determination of relations between the Business Excellence and Sustainability. Cross-cultural comparison of Business Excellence core values in the anal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(14 citation statements)
references
References 32 publications
0
8
0
Order By: Relevance
“…However, the People criterion (3) of the 2013 model is not directly related to a 2020 model criterion and is now spread across several criteria of the EFQM 2020 model, with People as a critical organizational stakeholder: criterion 1. In a literature review about national quality awards and business excellence models, Jankalová and Jankal [46] concluded that there is a relationship between business excellence and sustainability dimensions. The EFQM 2013 model encompassed "Creating a Sustainable Future" within the fundamental concepts of excellence, calling for the "integration of the concepts of sustainability within the organization core strategy, value chain and process design and allocating the resources required to deliver these goals".…”
Section: High Correlation Between Sub-criteria Medium Correlation Betmentioning
confidence: 99%
“…However, the People criterion (3) of the 2013 model is not directly related to a 2020 model criterion and is now spread across several criteria of the EFQM 2020 model, with People as a critical organizational stakeholder: criterion 1. In a literature review about national quality awards and business excellence models, Jankalová and Jankal [46] concluded that there is a relationship between business excellence and sustainability dimensions. The EFQM 2013 model encompassed "Creating a Sustainable Future" within the fundamental concepts of excellence, calling for the "integration of the concepts of sustainability within the organization core strategy, value chain and process design and allocating the resources required to deliver these goals".…”
Section: High Correlation Between Sub-criteria Medium Correlation Betmentioning
confidence: 99%
“…The creation value of Muslim fashion consists of preparing, responding, and recovering [27]. Furthermore, in order to stay resilient, the COVID-19 pandemic has forced the Muslim fashion industry to be adaptive, collaborative, innovative, and creative in order to develop new products based on types of consumer feedback such as OPRs [6], as well as to improve service and product quality [28]. These changes require the fashion industry to be more innovative and adaptable in order to reduce the spread of COVID-19 [29].…”
Section: Oprs Are Used To Support the Resilience Of Muslim Fashion In...mentioning
confidence: 99%
“…Some companies try to use management procedures in their activities, they want to achieve business excellence, which is also addressed in the study where the basis for achieving Business Excellence is to respect the core principles of TQM (Total Quality Management). [14] Other companies like to they use creativity and influence their results to achieve their goal.…”
Section: Creative Accountingmentioning
confidence: 99%